The Correlation Between Adolescent Social Behavior and Father Absence - Alfifah, Bella; Ariyati, Ika; Hendar, Kus (International Journal on Advanced Science, Education, and Religion, 2025)
This The purpose of this study is to find out how adolescent social behavior is related to fatherless status. The absence of a father figure in a child's life, both physically and emotionally, is referred to as fatherless status. Social behavior is the way a person interacts well with others such as cooperating, empathizing, and communicating. This study used a correlational quantitative method with 118 respondents from Ibs Nur Shofin Junior High School. This study used the Father-Love Absence Scale (FLAS) instrument used to measure fatherless status and the Social Skills Improvement System-Rating Scale (SSIS-RS) used to measure adolescent social behavior. Assumption tests including normality and linearity were conducted, and the results showed that the assumptions were met for the Pearson correlation test to be used. The results showed a significant moderate negative relationship between social behavior and fatherless status (r = -0.416, p < 0.01). That is, the higher the level of fatherlessness, the lower the social behavior exhibited by adolescents. This study confirms the important role fathers play in supporting adolescents' social development and may serve as a basis for social and educational interventions.